Portable automatic clothes dryer rack powered by battery of solar charger / Ahmad Ibrahim Abdul Malek - Abdul Malek, Ahmad Ibrahim (2013)
This diesis describes the design and construction of an automatic cloth dryer system model using a PIC 16F877A chip. The PIC chip is programmed to control the operation of clothes dryer system when it is raining day or when the surrounding started to become dark. The study is based on the principle of sensor detection and then the system is programmed to cover the clothes when it’s getting feedback from the sensor. The methodology of the project was started by constructing the model of the project. After that, design the circuit in Proteus software and do the programming in MPLab.